Community structure of demersal fish resources based on the depth of the waters in the South China Sea (Indonesia Fisheries Management Zone 711) - Robet Perangin angin; Sulistiono Sulistiono; Rahmat Kurnia; Achmad Fahrudin; Ali Suman (Jurnal Iktiologi Indonesia, 2017)
Information on distribution and community structure of demersal fish resources are important to be known as an input to the management of demersal fisheries. This study aimed to analyze the diversity and distribution of demersal fish resources based on the differences in the depth of the waters and the linkages to the environment. Research conducted in the South China Sea in May to June 2015 by operating a trawl gear in the station preset. The method of analysis of demersal fish diversity use some ecological indices i.e Margalef species richness index, Shannon-Wiener diversity index, Pielou evenness index, and Simpson dominance index. The ecological index value then associated with environmental conditions, using principal component analysis. Distribution of the ecological index indicated the stability of communities demersal fish resources getting better with the increase of depth. The most affected to the level of species richness and distribution of demersal fish were the parameters of depth, temperature and salinity, while the abundance distribution of fishes were associated with dissolved oxygen, and water transparency. The implication, that the water environmental conditions greatly affected the distribution and abundance of demersal fish. Abstrak Informasi mengenai persebaran dan struktur komunitas sumber daya ikan demersal penting sebagai bahan masukan untuk pengelolaan perikanan demersal. Penelitian ini bertujuan untuk menganalisis tingkat keanekaragaman dan persebaran sumber daya ikan demersal berdasarkan perbedaan kedalaman perairan, serta keterkaitannya dengan lingkungan. Penelitian dilaksanakan di Laut Cina Selatan pada bulan Mei sampai Juni 2015 dengan mengoperasikan alat tangkap pukat ikan di stasiun yang telah ditetapkan. Metode analisis keanekaragaman hayati ikan demersal menggunakan beberapa indeks ekologi yaitu indeks kekayaan jenis Margalef, indeks keanekaragaman Shannon-Wiener, indeks keseragaman Pielou, dan indeks dominansi Simpson. Nilai indeks ekologi tersebut kemudian dikaitkan dengan kondisi lingkungan, menggunakan analisis komponen utama. Hasil penelitian menunjukkan tingkat kestabilan komunitas sumber daya ikan demersal semakin baik seiring dengan meningkatnya kedalaman. Kedalaman, suhu, dan salinitas merupakan parameter yang paling memengaruhi tingkat kekayaan jenis serta persebaran sumber daya ikan demersal, sedangkan persebaran kelimpahan ikan sangat terkait dengan oksigen terlarut dan kecerahan perairan. Implikasinya, kondisi lingkungan perairan sangat memengaruhi persebaran dan kelimpahan ikan demersal.